Lymphadenopathy and synovial hyperplasia are associated with sepsis risk in an experimental model of rheumatoid arthritis - Aleith, Johann; Bergmann-Ewert, Wendy; Müller-Hilke, Brigitte (Frontiers in Immunology, 2025)
Sepsis is a life-threatening condition arising from immune dysregulation, particularly in patients with underlying diseases like rheumatoid arthritis (RA). However, experimental data on this phenomenon are lacking. Using flow cytometry, we investigated immune responses in mice with or without collagen-induced arthritis (CIA) following Streptococcus infection. Mice without CIA effectively cleared the infection, maintained hematopoiesis, and mobilized lymphocytes. In contrast, CIA mice exhibited impaired bacterial clearance, leukopenia, and sepsis. Emergency hematopoiesis in CIA mice led to depletion of lineage-committed progenitor cells, correlating with an accumulation of immature neutrophils that exhibited diminished cytokinogenesis. Notably, immune dysregulation in CIA mice appeared before sepsis onset. We detected an increase in neutrophils and monocytes in draining lymph nodes and joints. Importantly, lymphadenopathy and hyperactivated synovial fibroblasts, along with articular immune cell infiltration, drove excessive cytokine production, increasing sepsis risk. Our findings emphasize the importance of rigorous medical management of RA to mitigate infection-related complications.